Substitution of ethambutol with linezolid during the intensive phase of treatment of pulmonary tuberculosis: study protocol for a prospective, multicenter, randomized, open-label, phase II trial. Issue 1 (December 2017) - Lee, Ji; Kim, Deog; Lee, Jung-Kyu; Yoon, Ho; Jeong, Ina; Heo, Eunyoung; Park, Young; Lee, Jae; Park, Sung; Lee, Sang-Min; Lee, Chang-Hoon; Lee, Jinwoo; et al.
Abstract Background Linezolid, an oxazolidinone, substantially improves treatment outcomes of multidrug-resistant tuberculosis and extensively drug-resistant tuberculosis. We started a trial to test whether the use of linezolid instead of ethambutol could increase the rate of sputum culture conversion as of 8 weeks of treatment in patients with drug-susceptible tuberculosis. Methods/design This is a phase II, multicenter, randomized study with three arms. We are enrolling patients with pulmonary tuberculosis without rifampicin resistance screened by the Xpert MTB/RIF® assay. The standard treatment arm uses isoniazid (6 months), rifampicin (6 months), pyrazinamide (2 months), and ethambutol (2 months). Experimental arm 1 uses linezolid (600 mg/day) for 4 weeks instead of ethambutol. Experimental arm 2 uses linezolid (600 mg/day) for 2 weeks instead of ethambutol. The primary outcome is the sputum culture conversion rate on liquid media after 2 months of treatment. Secondary outcomes include the sputum culture conversion rate on solid media after 2 months of treatment, time to sputum culture conversion on liquid and solid media, cure rate, and treatment success rate. The frequencies of total adverse events (AEs) and serious AEs will be described and documented. Based on an α = 0.05 level of significance, a power of 85%, a 15% difference in the culture conversion rate after 2 months between the control arm and experimental arm 1 (75% vs. 90%), a 10% default (loss to follow-up) rate, and a 10% culture failure, the required number per arm was calculated to be 143 (429 in total). Discussion This trial will reveal the effectiveness and safety of 2 or 4 weeks of use of linezolid instead of ethambutol for patients with drug-susceptible pulmonary tuberculosis. If a new regimen including linezolid shows a higher culture conversion rate by week 8, and is safe, it could be tested as a 4-month antituberculosis treatment regimen in the future. Trial registration ClincalTrials.gov, NCT01994460 . Registered on 13 November 2013.